CCAFS reporting and evaluation in a results-based management framework - Schuetz, Tonya; Förch, Wiebke; Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This document summarizes the learning from the results-based management process and makes suggestions concerning the reporting and evaluation part of the impact pathway-based project management cycle, including the evaluation process of the trial projects.